2002
DOI: 10.1191/0269215502cr543oa
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous electrical stimulation may enhance sensorimotor recovery in chronic stroke

Abstract: Cutaneous stimulation had positive effects in the motor performance, limb sensation and the configuration of SEP of the paretic limb in chronic stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 22 publications
3
126
3
3
Order By: Relevance
“…Using functional MRI in study with healthy subjects, Golaszewski et al 7 found that applying cutaneous electrical stimulation to the hand by a wire-mesh glove for 20 minutes produced increased blood flow in the primary sensory cortex as well as primary and secondary motor cortices. In another study with hemiparetic patients, Peurala et al 8 showed that cutaneous stimulation of the affected hand or foot by a glove electrode or a sock electrode twice daily, 20 minutes each time for 3 weeks, improved limb sensation and motor performance together with somatosensory evoked potential normality classification of the paretic limbs.…”
mentioning
confidence: 98%
“…Using functional MRI in study with healthy subjects, Golaszewski et al 7 found that applying cutaneous electrical stimulation to the hand by a wire-mesh glove for 20 minutes produced increased blood flow in the primary sensory cortex as well as primary and secondary motor cortices. In another study with hemiparetic patients, Peurala et al 8 showed that cutaneous stimulation of the affected hand or foot by a glove electrode or a sock electrode twice daily, 20 minutes each time for 3 weeks, improved limb sensation and motor performance together with somatosensory evoked potential normality classification of the paretic limbs.…”
mentioning
confidence: 98%
“…Previous studies predominantly recruited participants months or even years after stroke and therefore may have treated the late complications of stroke rather than influenced recovery. 15,33,36 We applied sNMES to the shoulder as models of upper limb recovery suggest that proximal precede distal changes. 37 The regime has been shown to be beneficial in previous studies 13,31 and is widely accepted in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The perceptual threshold for electrocutaneous detection on the thumb surface has been documented as 1.5mA delivered at 3Hz, producing a two point discrimination distance of approximately 5.6 ± 1mm [86], targeting both the FA-I and FA-II afferent receptors. Cutaneous electrostimulation has demonstrated positive effects on motor performance, limb sensation and the configuration of Sensory Evoked Potentials of the paretic limb in people with chronic stroke [87]. However, a high degree of variability in the perception of electrocutaneous stimuli has been reported, with qualitative reports of electrotactile sensations ranging from tingles to burning pain, depending on the voltage and current applied; this variability has also been reported in individual participants between sessions [87].…”
Section: Perception Of Electrocutaneous Stimulationmentioning
confidence: 99%
“…Cutaneous electrostimulation has demonstrated positive effects on motor performance, limb sensation and the configuration of Sensory Evoked Potentials of the paretic limb in people with chronic stroke [87]. However, a high degree of variability in the perception of electrocutaneous stimuli has been reported, with qualitative reports of electrotactile sensations ranging from tingles to burning pain, depending on the voltage and current applied; this variability has also been reported in individual participants between sessions [87]. One caveat in the use of this type of stimulation is that the distinction between detection of electrical stimulation and pain perception is, on average, only 15dB, which contrasts to a dynamic range of 60-80dB for vibrotactile stimulation [88].…”
Section: Perception Of Electrocutaneous Stimulationmentioning
confidence: 99%